Adherence to WCRF/AICR cancer prevention recommendations and metabolic syndrome in breast cancer patients. Issue 1 (28th July 2015) - Bruno, Eleonora; Gargano, Giuliana; Villarini, Anna; Traina, Adele; Johansson, Harriet; Mano, Maria Piera; Santucci De Magistris, Maria; Simeoni, Milena; Consolaro, Elena; Mercandino, Angelica; Barbero, Maggiorino; Galasso, Rocco; et al.
<x xml:space="preserve">Abstract</x> Metabolic syndrome (MetS), conventionally defined by the presence of at least three out of five dismetabolic traits (abdominal obesity, hypertension, low plasma HDL‐cholesterol and high plasma glucose and triglycerides), has been associated with both breast cancer (BC) incidence and prognosis. We investigated the association between the prevalence of MetS and a score of adherence to the World Cancer Research Fund (WCRF) and American Institute for Cancer Research (AICR) recommendations for the prevention of cancer in a cross‐sectional study of BC patients. The DIet and ANdrogen‐5study (DIANA‐5) for the prevention of BC recurrences recruited 2092 early stage BC survivors aged 35–70. At recruitment, all women completed a 24‐hour food frequency and physical activity diary on their consumption and activity of the previous day. Using these diaries we created a score of adherence to five relevant WCRF/AICR recommendations. The prevalence ratios (PRs) and 95% confidence intervals (CIs) of MetS associated with the number of recommendations met were estimated using a binomial regression model. The adjusted PRs of MetS decreased with increasing number of recommendations met (p < 0.001). Meeting all the five recommendations versus meeting none or only one was significantly associated with a 57% lower MetS prevalence (95% CI 0.35–0.73). Our results suggest that adherence to WCRF/AICR recommendations is a major determinant of MetS and may have a clinical impact.